Bacterial ‘Grounded’ Prophages: Hotspots for Genetic Renovation and Innovation - Ramisetty, Bhaskar Chandra Mohan; Sudhakari, Pavithra Anantharaman (Frontiers in Genetics, 2019)
Bacterial genomes are highly plastic allowing the generation of variants through mutations and acquisition of genetic information. The fittest variants are then selected by the econiche thereby allowing the bacterial adaptation and colonisation of the habitat. Larger genomes, however, may impose metabolic burden and hence bacterial genomes are optimised by the loss of frivolous genetic information. The activity of temperate bacteriophages has acute consequences on the bacterial population as well as the bacterial genome through lytic and lysogenic cycles. Lysogeny is a selective advantage as the prophage provides immunity to the lysogen against secondary phage attack. Since the non-lysogens are eliminated by the lytic phages, lysogens multiply and colonise the habitat. Nevertheless, all lysogens have an imminent risk of lytic cycle activation and cell lysis. However, a mutation in the attachment sites or in the genes that encode the specific recombinase responsible for prophage excision could result in ‘grounding’ of the prophage. Since the lysogens with grounded prophage are immune to respective phage infection as well as dodge the induction of lytic cycle, we hypothesise that the selection of these mutant lysogens is favoured relative to their normal lysogenic counterparts. These grounded prophages offer several advantages to the bacterial genome evolution through propensity for genetic variations including inversions, deletions, and insertions via horizontal gene transfer. We propose that the grounded prophages expedite bacterial genome evolution by acting as ‘genetic buffer zones’ thereby increasing the frequency as well as the diversity of variations on which natural selection favours the beneficial variants. The grounded prophages are also hotspots for horizontal gene transfer wherein several ecologically significant genes such as those involved in stress tolerance, antimicrobial resistance, and novel metabolic pathways, are integrated. Moreover, the high frequency of genetic changes within prophages also allows proportionate probability for the de novo genesis of genetic information. Through sequence analyses of well-characterized E. coli prophages we exemplify various roles of grounded prophages in E. coli ecology and evolution. Therefore, the temperate prophages are one of the most significant drivers of bacterial genome evolution and sites of biogenesis of genetic information.